Single molecule spectroscopic studies of solute nanoconfinement in nanoporous membranes and on surfaces - Rashidi, Hamid (My University, 2025)
This dissertation investigates the mass transport of molecules confined within anodic aluminum oxide (AAO) membranes and on PET microplastic surfaces, using fluorescence correlation spectroscopy (FCS) as a single-molecule detection technique. Rhodamine B (RhB) was employed as a fluorescent probe to study molecular dynamics and surface interactions. The first study focuses on understanding how solvent mixtures and solutes behave under nanoconfinement. To this end, RhB diffusion within 10 nm and 20 nm diameter AAO nanopores filled with ethanol/water mixtures was examined, with solvent compositions ranging from pure ethanol to pure water. The results revealed two distinct diffusion mechanisms, with mean diffusion coefficients, Df (fast) and Ds (slow), differing by nearly two orders of magnitude. Both Df and Ds were found to increase with pore size and were significantly lower than the bulk diffusion coefficient (Db) of RhB in the free solution. The fast diffusion component, closely related to mixture viscosity, represents hindered bulk-like diffusion in the central pore regions and is influenced by hydrodynamic drag and electrostatic interactions with the nanopore surface. In contrast, slow diffusion likely involves the adsorption of RhB to the pore walls governed by an adsorption-mediated mechanism. Trends in the autocorrelation amplitude and Ds exhibited a strong dependence on solvent composition, mimicking RhB solubility behavior. Ds was smallest in pure ethanol and pure water and largest in intermediate mixtures, suggesting that RhB surface adsorption is strongest in the pure solvents and weakest where the dye is most soluble in intermediate mixtures. The second study applies confocal fluorescence correlation spectroscopy (FCS) to investigate organic molecules adsorbed from aqueous solutions onto the surfaces of both virgin and post-consumer synthetic microplastics. The investigation includes fresh and artificially aged polyethylene terephthalate (PET) plastics, with the aging process meticulously conducted in a UV-ozone chamber. Raman spectroscopy confirms the composition of the PET microplastics, while water contact angle measurements and surface roughness analyses reveal increased wettability and changes in surface texture with aging, consistent with surface oxidation. Rhodamine B (RhB) dye, used as a fluorescent probe in the FCS experiments, serves as an analog for organic pollutants commonly found on microplastics. FCS results demonstrate dye accumulation on the PET surfaces as the plastics age, with significantly slower dye motion on the surfaces compared to the bulk aqueous solution. The dye undergoes anomalous subdiffusion on the PET surfaces, with diffusion rates slowing dramatically and becoming more anomalous as the plastics age. The reduced mobility is likely due to ionic interactions or hydrogen bonding between the dye molecules and the oxidized plastic surfaces. These findings offer critical new insights into how microplastics accumulate and transport organic pollutants as they undergo environmental weathering, contributing to our understanding of the risks associated with microplastic pollution.
Keywords: Single molecule spectroscopy; Nanoconfinement; Nanoporous membranes